EFEKTIFITAS EKSTRAK KERING DAUN SALAM (SYZIGIUM POLYANTHUM (WIGHT) WALP) TERHADAP PENURUNAN KADAR KOLESTEROL PADA LANSIA - Siswiyanti, Siswiyanti; Rosalinna, Rosalinna (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Bay leaves have chemical contents, namely tannins, flavonoids, and 0.05% essential oil consisting of eugenol and citral. The content of Eugenia polyantha is an active ingredient that is thought to have pharmacological effects. Tannins and flavonoids are active ingredients that have anti-inflammatory and antimicrobial effects, while essential oils have analgesic effects. herbal plants to get drugs that can be good in reducing levels of triglycerides and cholesterol and have very minimal side effects in the future. The purpose of this study was to determine the effectiveness of effectiveness of dried bay leaf extract (Syzygium polyanthum (Wight) Walp) on reducing cholesterol levels in the elderly in Klaten district. The research method used was one-way ANOVA to determine the effectiveness of bay leaf extract 5 mg 2 times a day and 10 mg bay leaf extract 1 time a day in the elderly. The results of this study are the same or different average test (ANOVA analysis) obtained a significance value of 0.233 <0.05, it can be concluded that the average dose of 5 mg and 10 mg bay leaf extract in group 1 and group 2 are the same.